Post-traumatic headache Cefaléia após traumatismo cranioencefálico - Hugo André de Lima Martins; Valdenilson Ribeiro Ribas; Bianca Bastos Mazullo Martins; Renata de Melo Guerra Ribas; Marcelo Moraes Valença (Arquivos de Neuro-Psiquiatria)
The onset of post-traumatic headache (PTC) occurs in the first seven days after trauma, according to the International Headache Society (IHS) classification. The objective of this study was to evaluate the several forms of headache that appear after mild head injury (HI) and time interval between the HI and the onset of pain. We evaluated 41 patients with diagnosis of mild HI following the IHS criteria. Migraine without aura and the chronic tension-type headache were the most prevalent groups, occurring in 16 (39%) and 14 (34.1%) patients respectively. The time interval between HI and the onset of headache was less than seven days in 20 patients (48.7%) and longer than 30 days in 10 (24.3%) patients. The results suggest that PTC may arise after a period longer than is accepted at the present by the IHS. O início da cefaléia pós-traumática (CPT) ocorre dentro de sete dias após o trauma, de acordo com a classificação da Sociedade Internacional de Cefaléia (SIC). O objetivo deste estudo foi avaliar as diversas formas de cefaléia que surgem após o traumatismo cranioencefálico (TCE) leve e o intervalo de tempo entre o TCE e o início da dor. Foram avaliados 41 pacientes com diagnóstico de cefaléia pós-traumática leve segundo os critérios da SIC. Migrânea sem aura e cefaléia do tipo tensional crônica foram os tipos de cefaléia mais comuns, ocorrendo em 16 (39%) e 14 (34,1%) dos pacientes respectivamente. O intervalo de tempo entre o TCE e o início da cefaléia foi menor que sete dias em 20 pacientes (48%) e maior que 30 dias em 10 (24,3%) pacientes. Estes resultados sugerem que a CPT pode surgir após período maior do que é aceito atualmente pela SIC.